A variational approach towards the modeling of equilibrium twin interfaces in a single-crystalline magnetic shape memory alloy sample - Wang, Jiong; Steinmann, Paul (Proceedings in applied mathematics and mechanics, 2014)
In this work, a variational approach is proposed to study the magneto‐mechanical response of a single‐crystalline MSMA sample. By proposing a total energy functional for the whole magneto‐mechanical system, the governing PDE system is derived by calculating the variations of the total energy functional with respect to the independent variables. An iterative numerical algorithm is proposed to solve the governing PDE system. As an example, a MSMA sample with cuboid shape and subject to perpendicularly applied magnetic and mechanical loadings is considered. It can be seen that the magneto‐mechanical response of this sample can be predicted at a quantitative level. The whole procedure of variant reorientation in the sample can also be simulated. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)